Postural sway, working years and BMI in healthy truck drivers: an observational study. Issue 7 (12th July 2017) - Ohlendorf, Daniela; Troebs, Paul; Lenk, Andreas; Wanke, Eileen; Natrup, Jörg; Groneberg, David
Abstract : Objectives: The following study analyses the influence of risk factors among the occupational group of truck drivers on postural control and body mass index (BMI). Design: Observational study. Setting: One motorway station close to several highways in Germany. Participants: 180 truck drivers (177 male/3 female), aged 21–65 years old, took part in this study. Outcome measures: Postural control was examined using a pressure plate. In order to examine the influence of body weight (BMI) and working years on postural control, subjects were divided into samples of five and three groups, respectively. Furthermore, it was evaluated whether the subjects suffered from back pain. For data analysis, the Kruskal-Wallis test was used as the data were not normally distributed. Once the p value of the Kruskal-Wallis test was p≤0.05,  the Conover-Iman comparison and afterwards the Bonferroni-Holm correction were used. The significance level was set at α ≤0.05. Results: Regarding the number of working years, a significant increase of frontal (p≤0.04) and sagittal (p≤0.001) sway were observed. The correlation of the five BMI groups with the number of working years demonstrates that an increase of the working years leads to an increase of BMI (p≤0.03). Furthermore, the majority of truck drivers participating in this study suffered from back pain (61.7%). Conclusions: BMI and musculoskeletal impairment are indicators of health risk factors. In this study, it is shown that an increasing number of working years and an increasing BMI lead to a decrease in frontal and sagittal postural sway. In addition, the number of working years correlates with body weight and back pain.